Anodal tDCS improves attentional control in older adults - Claire Hanley (Experimental Gerontology, 2019)
To provide insight into the benefits of tDCS, this study used an age-optimised stimulation protocol whereby key parameters (amplitude, duration, and electrode configuration) were selected in accordance with knowledge of stimulation effects, specific to the ageing brain. Participants completed three sessions of double-blind, anodal or sham stimulation, in conjunction with a novel task switching paradigm. The results show that only those who were administered anodal tDCS exhibited an increase in task switching speed (p < .01, d = 1.36).